Management of acute bone loss following high grade open tibia fractures: Review of evidence on distraction osteogenesis and induced membrane techniques - Benulic, Crt; Canton, Gianluca; Gril, Iztok; Murena, Luigi; Kristan, Anze (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Optimal treatment for acute post-traumatic bone loss in the tibia remains unclear. Distraction osteogenesis (DO) and induced membrane technique (IM) have been established as the mainstays of treatment. Aim of this article is to review the current evidence regarding the use of these two methods. Methods: A review of the MEDLINE database was performed with strict inclusion and exclusion criteria focusing on treatment of the acute bone loss after open tibia fractures with DO and IM. Bone union rate was taken as the primary outcome and infection rate as secondary outcome. Results: Four studies out of 78 on the use of the DO and three studies out of 18 on the use of the IM technique matched the inclusion criteria. Union rate in the DO group ranged between 92% and 100%, with infection rates between 0 and 4%. In the IM group, union was reached in 42% to 100% of cases, with septic complications occurring in 12% to 43%. Differences in union rate and infection rate reached statistical significance. Discussion: We found a considerable evidence gap regarding treatment of bone loss in high grade open tibia fractures. The limitations of our study prevented us from drawing clear causative conclusions on the results. Although our study points to higher union rates and lower infection rate with the use of the DO technique, the results remain preliminary and further high-level evidence is needed to establish the roles of DO and IM in treatment of acute bone loss in open tibia fractures.